Potassium Quantification for Wheat (Triticum Aestivum L.) under the Agroecological Conditions of District Swabi - Rehmani, Urooj; Manzoor, Danish; Jalal, Rashid; Khan, Muhammad Mehdi; Mansoor, Muhammad Abdullah Khan; Shah, Iftikhar; Hamzeh, Muhammad; Mastoi, Abdul Hafeez; Shar, Sadam Hussain; Ali, Majid (Journal of Agriculture and Biology, 2025)
The present study was conducted at Agriculture Research Station Bamkhel, District Swabi, Khyber Pakhtunkhwa, Pakistan to observe the effect of different potassium (K2O) levels on wheat productivity. Wheat variety Pirsabak-2004 was tested for different potassium (K2O) levels of 0, 60, 70, 80, 90 and 100 kg ha-1. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Statistical analysis of the data showed a significant (P≤0.05) effect of different potassium (K2O) levels on emergence m-2, tillers m-2, 1000 grains weight (g) and grain yield (kg ha-1) while a non-significant (P>0.05) effect on leaf area (cm2), plant height (cm), spike length (cm) and grains spike-1. The data revealed highest leaves plant-1 (5.66) and plant height (86.66 cm) for potassium (K2O) level of 60 kg ha-1. The results further indicated highest leaf area (45.53 cm2) for plots treated with potassium (K2O) level of 70 kg ha-1. Similarly, maximum tillers (192.44 m-2), spike length (10.33 cm), 1000 grains weight (35.33g) and grain yield (5168 kg ha-1) were recorded for plots applied with potassium (K2O) at the rate of 80 kg ha-1. The maximum emergence (48.66 m-2) and grains spike-1 (40.86) were noted for potassium (K2O) level of 90 kg ha-1. It was concluded that potassium (K2O) level of 80 kg ha-1 resulted in maximum growth and yield components than all other treatments under study.
Keywords: Potassium; fertilizer; wheat; grain yield